Estimating the benefit of a second bone anchored hearing implant in unilaterally implanted users with a testband. (2nd April 2016) - Kompis, Martin; Kurz, Anja; Flynn, Mark; Caversaccio, Marco
Abstract: Conclusion Using a second bone anchored hearing implant (BAHI) mounted on a testband in unilaterally implanted BAHI users to test its potential advantage pre-operatively under-estimates the advantage of two BAHIs placed on two implants. Objectives To investigate how well speech understanding with a second BAHI mounted on a testband approaches the benefit of bilaterally implanted BAHIs. Method Prospective study with 16 BAHI users. Eight were implanted unilaterally (group A) and eight were implanted bilaterally (group B). Aided speech understanding was measured. Speech was presented from the front and noise came either from the left, right, or from the front in two conditions for group A (with one BAHI, and with two BAHIs, where the second device was mounted on a testband) and in three conditions for group B (same two conditions as group A, and in addition with both BAHIs mounted on implants). Results Speech understanding in noise improved with the additional device for noise from the side of the first BAHI (+0.7 to +2.1 dB) and decreased for noise from the other side (−1.8 dB to −3.9 dB). Improvements were highest (+2.1 dB, p  = 0.016) and disadvantages were smallest (−1.8 dB, p  = 0.047) with both BAHIs mounted on implants. Testbands yielded smaller advantages and higher disadvantages of the additional BAHI (average difference = −0.9 dB).